Cult Violence in Nigeria and Corporate Social Responsibility in Oil Producing Communities - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2023)
Since the beginning of 2014, reports of cult violence have increased sharply in the Nigeria's oil producing communities. Hence, we set out to examine the role of corporate social responsibility (CSR) from multinational oil companies (MOCs) in mitigating the spread of cult group violence in the region. A total of two thousand four hundred respondents were sampled across the nine states of the Niger Delta. Results from the use of estimated logit model reveal that MOCs via Global Memorandum of Understanding (GMoU) are in good position to deter the aggression and rise of cult violence using interventions for youth as a priority target group mechanism. This calls for pro-youth capacity building programmes, specially designed to equip the clusters with appropriate skills required for peaceful engagement and to complement government efforts in the planning and implementation of the development agenda for their respective communities. In turn, this will contribute towards enhancing a peaceful environment for doing business in the Niger Delta region.
Keywords: 330; Environmental justice; cult violence; corporate social responsibility; oil producing communities; sub-Saharan Africa